Modified composite solid electrolyte as well as preparation method and application thereof
By mixing yang ions and halogen ions in oxide solid electrolytes, and wrapping flexible polymer fiber layer and rotor whole fluoride carboxylic acid, the mechanical rigidity and water absorption of solid electrolyte are solved. Compound solid electrolyte.
Patent Information
- Application Number
- CN202411589525.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-01-28
AI Technical Summary
The existing oxide solid electrolytes have problems such as difficult mechanical rigidity to dopant, bulk electron conductivity leads to lithium dendrites, and water absorption affects battery performance.
Use a composite solid electrolyte doped with cations and halogen anion, and wrap the flexible polymer fiber layer and the whole fluorofluctial carboxylic acid salt on its surface to improve the softness of the material, reduce water absorption and reduce water Improve stability.
A modified composite solid electrolytes with high ionic conductivity, high degree of flexibility, high moisture improvement effects, and stable material structure have improved the performance and stability of lithium ion batteries.
Smart Images

Figure BDA0005126807530000281 
Figure BDA0005126807530000291 
Figure HDA0005126807610000011
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries, and in particular relates to a modified composite solid electrolyte, a preparation method and application thereof. Background Art
[0002] In modern society, batteries are key to powering many devices, including smartphones, laptops, electric vehicles, and renewable energy grids. As demand for portable electronics and electric vehicles (EVs) continues to increase, the need for high-performance, long-life, and safe batteries is becoming increasingly urgent. Advances in battery technology can greatly impact the way people live and work, from achieving sustainable energy to reducing dependence on fossil fuels. Unfortunately, lithium-ion batteries have safety issues and problems with how to further increase energy density. Therefore, it is imperative to strengthen research on battery technology.
[0003] Oxide inorganic solid electrolytes have high ionic conductivity and can therefore provide a stable and efficient transport medium for the ion flow between the anode and cathode in the battery. In addition, solid electrolytes can prevent side reactions between the electrode and the electrolyte, thereby avoiding the formation of dendrites and improving the overall energy density of the battery. For example, lithium aluminum titanium phosphate (LATP) has high ionic conductivity, chemical stability and low reactivity with lithium metal anodes; lithium lanthanum zirconium oxide (LLZO) has favorable properties such as ionic conductivity, energy density, chemical stability, electrochemical stability, air stability, thermal stability and safety. They have great potential in promoting the development of energy storage and paving the way for safer, more efficient and more environmentally friendly batteries.
[0004] However, from the physical properties of oxide solid electrolytes, it can be found that they have inherent mechanical rigidity, and it is challenging to uniformly dope / coat them on the surface of the material; in addition, their significant bulk electronic conductivity may inadvertently promote the formation of lithium dendrites at the interface between lithium and solid electrolyte, as well as the growth and penetration of dendrites along grain boundaries.
[0005] Moreover, from the crystal structure of oxide solid electrolyte, due to the presence of oxygen-containing groups, water molecules can be adsorbed on the surface. The introduction of water has a crucial impact on the performance of lithium-ion batteries. Water is a key factor that needs to be strictly controlled during the production process of lithium-ion batteries. Excessive water can not only lead to the decomposition of lithium salts in the electrolyte and have a certain degree of corrosion and damage to positive and negative electrode materials and current collectors, but also lead to a decrease in the cycle performance and safety performance of the battery.
[0006] Therefore, the problems existing in existing oxide solid electrolytes need further analysis and in-depth research. Summary of the invention
[0007] In view of this, the technical problem to be solved by the present invention is to provide a modified composite solid electrolyte with higher ionic conductivity, higher softness, lower water absorption and higher stability, and a preparation method and application thereof.
[0008] The present invention provides a modified composite solid electrolyte, comprising: a composite solid electrolyte, a flexible polymer fiber layer wrapped on the surface of the composite solid electrolyte, and a perfluorocarboxylic acid and / or a perfluorocarboxylate grafted on the flexible polymer fiber layer;
[0009] The composite solid electrolyte is a solid electrolyte doped with cations and halogen anions;
[0010] The cations are selected from transition metal cations and / or metalloid cations.
[0011] Preferably, the composite solid electrolyte is selected from lithium aluminum titanium phosphate doped with cations and halogen anions;
[0012] And / or, the flexible polymer in the flexible polymer fiber layer is selected from one or more of polyester, polyamide, polyvinyl alcohol and polyacrylonitrile;
[0013] and / or, the number of carbon atoms of the perfluorocarboxylic acid and / or perfluorocarboxylate is 4 to 12;
[0014] And / or, the cation is selected from one or more of silicon ions, zirconium ions, tantalum ions and niobium ions.
[0015] Preferably, the molar ratio of cations, halogen anions and phosphorus in the lithium aluminum titanium phosphate doped with cations and halogen anions is (0.05-0.5): (0.05-0.5): (2.5-3);
[0016] And / or, the mass ratio of the flexible polymer fiber layer to the composite solid electrolyte is 1:(5-20);
[0017] And / or, the mass ratio of the total mass of the composite solid electrolyte and the flexible polymer fiber layer to the perfluorocarboxylic acid and / or perfluorocarboxylate is 5-50.
[0018] The present invention also provides a method for preparing a modified composite solid electrolyte, comprising the following steps:
[0019] S1) mixing a lithium source, an aluminum source, a titanium source, a phosphorus source, a compound containing a cation and a compound containing a halogen anion, sintering, and grinding to obtain a composite solid electrolyte; the cation is selected from transition metal cations and / or metalloid cations;
[0020] S2) mixing the composite solid electrolyte and the flexible polymer fiber in water, and drying to obtain a composite solid electrolyte wrapped by the flexible polymer fiber;
[0021] S3) mixing the composite solid electrolyte wrapped by the flexible polymer fiber with perfluorocarboxylic acid and / or perfluorocarboxylate in a solvent to obtain a modified composite solid electrolyte.
[0022] Preferably, the lithium source is selected from one or more of lithium carbonate, lithium hydroxide, lithium nitrate, lithium oxalate, lithium bicarbonate and lithium oxide;
[0023] The aluminum source is selected from aluminum oxide and / or aluminum hydroxide;
[0024] The titanium source is selected from titanium dioxide and / or titanium trioxide;
[0025] The phosphorus source is selected from one or more of phosphoric acid, diammonium phosphate and diammonium hydrogen phosphate;
[0026] The cation-containing compound is selected from one or more of silicon dioxide, silicon dioxide, zirconium dioxide, niobium pentoxide, and tantalum pentoxide;
[0027] The compound containing halogen anions is selected from one or more of ammonium fluoride, aluminum fluoride, calcium fluoride, ammonium chloride, calcium chloride, potassium chloride, ammonium bromide, potassium bromide, ammonium iodide and potassium iodide.
[0028] Preferably, the molar ratio of the lithium source, aluminum source, titanium source, phosphorus source, cation-containing compound and halogen anion-containing compound is (0.5-1): (0.1-0.5): (1.3-1.8): (2.5-3): (0.05-0.5): (0.05-0.5).
[0029] Preferably, the ball-to-material ratio in the step S1) is 5 to 20;
[0030] The grinding is wet grinding; the mass ratio of the liquid medium to the sintered powder in the wet grinding is 2 to 5;
[0031] The grinding time is 3 to 6 hours;
[0032] And / or, grinding and sieving to obtain a solid electrolyte doped with cations and halogen anions; the mesh number of the sieving sieve is 80 to 400 meshes.
[0033] Preferably, the flexible polymer fiber is prepared according to the following steps:
[0034] A1) mixing the flexible polymer powder with the DMF solution and allowing to stand to obtain a spinning solution;
[0035] A2) electrospinning the spinning solution to obtain flexible polymer fibers;
[0036] The mass concentration of the flexible polymer in the spinning solution is 5% to 15%;
[0037] The electrospinning flow rate is 0.2-0.5 mL / h;
[0038] The humidity of the electrospinning is 40% to 60%;
[0039] The receiving distance of the electrospinning is 10 to 20 cm;
[0040] The voltage of the electrostatic spinning is 10-20 kV.
[0041] The present invention also provides a battery, comprising a positive electrode, a separator and a negative electrode;
[0042] The positive electrode comprises the modified composite solid electrolyte described above;
[0043] The negative electrode includes the modified composite solid electrolyte.
[0044] Preferably, the positive electrode comprises a positive electrode active layer; the particle size of the modified composite solid electrolyte in the positive electrode active layer is 50 to 600 nm;
[0045] The mass concentration of the modified composite solid electrolyte in the positive electrode active layer is 0.5wt% to 10wt%;
[0046] The negative electrode includes a negative electrode active layer; the particle size of the modified composite solid electrolyte in the negative electrode active layer is 50 to 600 nm;
[0047] The mass concentration of the modified composite solid electrolyte in the negative electrode active layer is 0.5wt% to 20wt%.
[0048] The present invention provides a modified composite solid electrolyte, comprising: a composite solid electrolyte, a flexible polymer fiber layer wrapped on the surface of the composite solid electrolyte, and a perfluorocarboxylic acid and / or a perfluorocarboxylate salt grafted on the flexible polymer fiber layer; the composite solid electrolyte is a solid electrolyte doped with cations and halogen anions. Compared with the prior art, the modified composite solid electrolyte provided by the present invention increases the ionic conductivity of the material due to the doped cations and halogen anions, and at the same time improves the stability of the material, and the wrapping of the flexible hydrophobic polymer layer improves the rigid structure of the modified composite solid electrolyte, and also weakens the surface adsorption of water; in addition, the prepared mesh polymer layer is conducive to the rapid and effective transmission of lithium ions between the mesh structures, so that the modified composite solid electrolyte has the characteristics of high ionic conductivity, high flexibility, obvious moisture improvement effect, stable material structure, etc., and can be applied to lithium ion batteries to improve battery performance and stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 A schematic diagram of the preparation process of the modified composite solid electrolyte provided by the present invention;
[0050] Figure 2 The XRD diagrams of the powders of the modified composite solid electrolyte obtained in Example 1 of the present invention and the LATP obtained in Comparative Example 1 are shown. DETAILED DESCRIPTION
[0051] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0052] The present invention provides a modified composite solid electrolyte, comprising: a composite solid electrolyte, a flexible polymer fiber layer wrapped on the surface of the composite solid electrolyte, and a perfluorocarboxylic acid and / or a perfluorocarboxylate salt grafted on the flexible polymer fiber layer; the composite solid electrolyte is a solid electrolyte doped with cations and halogen anions; the cations are transition metal cations and / or metalloid cations.
[0053] According to the present invention, the composite solid electrolyte is preferably lithium aluminum titanium phosphate doped with cations and halogen anions; the molar ratio of cations, halogen anions and phosphorus element in the lithium aluminum titanium phosphate doped with cations and halogen anions is preferably (0.05-0.5): (0.05-0.5): (2.5-3), more preferably (0.08-0.15): (0.08-0.15): (2.85-3), more preferably (0.08-0.12): (0.08-0.12): (2.88-3), most preferably 0.1: 0.1: 2.9; the cations are transition metal cations and / or metalloid cations well known to those skilled in the art, without special restrictions, and specifically can be one or more of silicon ions, zirconium ions, tantalum ions and niobium ions; in the present invention, the cations are preferably provided by the oxide of the element; the halogen anions are well known to those skilled in the art The halogen anion can be any halogen anion without any special limitation, and can be one or more of fluoride ion, chloride ion, bromide ion and iodide ion; the molar ratio of lithium element, aluminum element, titanium element, phosphorus element, cation and halogen anion in the lithium aluminum titanium phosphate doped with halogen anions is preferably (0.5-1): (0.1-0.5): (1.3-1.8): (2.5-3): (0.05-0.5): (0.05-0.5), and more preferably The selected ones are (0.6~0.8):(0.1~0.4):(1.5~1.8):(2.85~3):(0.08~0.15):(0.08~0.15), and the preferred ones are 0.7:(0.2~0.3):(1.5~1.7):(2.88~3):(0.08~0.12):(0.08~0.12), and the most preferred ones are 0.7:0.2:1.6:2.9:0.1:0.1.
[0054] According to the present invention, the composite solid electrolyte is wrapped with a flexible polymer fiber layer, preferably a mesh flexible polymer fiber layer; the flexible polymer in the flexible polymer fiber layer is preferably one or more of polyester, polyamide, polyvinyl alcohol and polyacrylonitrile; the mass ratio of the flexible polymer fiber layer to the composite solid electrolyte is preferably 1: (5-20), more preferably 1: (5-15), more preferably 1: (8-12), and most preferably 1: 10.
[0055] According to the present invention, perfluorocarboxylic acid and / or perfluorocarboxylate are grafted onto the flexible polymer fiber layer; the number of carbon atoms of the perfluorocarboxylic acid and / or perfluorocarboxylate is preferably 4-12, more preferably 6-10, more preferably 7-11, and most preferably 8; in some embodiments provided by the present invention, one or more of perfluorooctanoic acid, perfluoroheptanoic acid, perfluorononanoic acid, perfluorohexanoic acid, perfluoropentanoic acid, perfluorobutyric acid, perfluorodecanoic acid and perfluorododecanoic acid are grafted onto the flexible polymer fiber layer; the mass ratio of the total mass of the composite solid electrolyte and the flexible polymer fiber layer to the perfluorocarboxylic acid and / or perfluorocarboxylate is 5-50, more preferably 8-50, more preferably 8-40, more preferably 8-30, and most preferably 8-20.
[0056] The modified composite solid electrolyte provided by the present invention increases the ionic conductivity of the material due to the incorporated cations and halogen anions, and at the same time improves the stability of the material. The wrapping of the flexible hydrophobic polymer layer improves the rigid structure of the modified composite solid electrolyte, and also weakens the adsorption of water on the surface. In addition, the prepared network polymer layer is conducive to the rapid and effective transmission of lithium ions between the network structures, so that the modified composite solid electrolyte has the characteristics of high ionic conductivity, high flexibility, obvious moisture improvement effect, stable material structure, etc., and can be applied to lithium ion batteries to improve battery performance and stability.
[0057] The present invention also provides a method for preparing a modified composite solid electrolyte, comprising the following steps: S1) mixing a lithium source, an aluminum source, a titanium source, a phosphorus source, a compound containing cations and a compound containing halogen anions, sintering, and grinding to obtain a composite solid electrolyte; S2) mixing the composite solid electrolyte with flexible polymer fibers in water, and drying to obtain a composite solid electrolyte wrapped by the flexible polymer fibers; S3) mixing the composite solid electrolyte wrapped by the flexible polymer fibers with perfluorocarboxylic acid and / or perfluorocarboxylate in a solvent to obtain a modified composite solid electrolyte.
[0058] See also Figure 1 , Figure 1 A schematic diagram of the preparation process of the modified composite solid electrolyte provided by the present invention.
[0059] The present invention has no particular limitation on the sources of all raw materials, and any raw materials available on the market can be used.
[0060] A lithium source, an aluminum source, a titanium source, a phosphorus source, a compound containing a cation and a compound containing a halogen anion are mixed; the lithium source can be a lithium source well known to those skilled in the art without any special restrictions, and in the present invention, it is preferably one or more of lithium carbonate, lithium hydroxide, lithium nitrate, lithium oxalate, lithium bicarbonate and lithium oxide; the aluminum source can be an aluminum source well known to those skilled in the art without any special restrictions, and in the present invention, it is preferably aluminum oxide and / or aluminum hydroxide; the titanium source can be a titanium source well known to those skilled in the art without any special restrictions, and in the present invention, it is preferably titanium dioxide and / or titanium trioxide; the phosphorus source can be a phosphorus source well known to those skilled in the art without any special restrictions, and in the present invention, it is preferably one or more of phosphoric acid, ammonium dihydrogen phosphate and diammonium hydrogen phosphate; the cation can be an oxide cation well known to those skilled in the art without any special restrictions, and specifically can be one or more of silicon ions, zirconium ions, tantalum ions and niobium ions; the cation-containing compound is preferably an oxide; the halogen anion-containing compound The compound containing halogen anions is any compound known to those skilled in the art, and is not particularly limited. In the present invention, it is preferably one or more of ammonium fluoride, aluminum fluoride, calcium fluoride, ammonium chloride, calcium chloride, potassium chloride, ammonium bromide, potassium bromide, ammonium iodide and potassium iodide; the molar ratio of the lithium source, aluminum source, titanium source, phosphorus source, the compound containing cationic compounds and the halogen anion is preferably (0.5-1): (0.1-0.5): (1.3-1.8): (2.5-3) 3: (0.05-0. 25): (0.05-0.5), more preferably (0.6-0.8): (0.1-0.4): (1.5-1.8): (2.85-3): (0.08-0.15): (0.08-0.15), more preferably 0.7: (0.2-0.3): (1.5-1.7): (2.88-3): (0.08-0.12): (0.08-0.12), most preferably 0.7: 0.2: 1.6: 2.9-3: 0.1: 0.1;
[0061] After mixing, sintering is performed to obtain a sintered powder; the sintering temperature is preferably 800°C to 1000°C; in some embodiments provided by the present invention, the sintering temperature is specifically 800°C, 850°C, 900°C, 950°C or 1000°C; the sintering time is preferably 12 to 24 hours.
[0062] The sintered powder is ground; the grinding method can be a grinding method well known to those skilled in the art without any special restrictions, and in the present invention, preferably planetary ball milling, stirred milling, sand milling and the like; the ball-to-material ratio of the grinding is preferably 5-20, more preferably 5-15, more preferably 5-10, more preferably 5-8, and most preferably 5; the grinding balls can be one or more of zirconia balls, alumina balls and agate balls; the diameter of the grinding balls is preferably 0.3-5 mm, more preferably 1-5 mm, more preferably 2-4 mm, and most preferably 3 mm; the grinding is preferably wet grinding; the mass ratio of the liquid medium to the sintered powder in the wet grinding is preferably (2-5):1; the liquid medium for the wet grinding can be a liquid medium well known to those skilled in the art without any special restrictions, and in the present invention, preferably one or more of deionized water, anhydrous ethanol, isopropanol and N-methylpyrrolidone; the grinding time is preferably 3-6 h.
[0063] After grinding, it is preferably dried and sieved to obtain a composite solid electrolyte; the drying temperature is preferably 80°C to 120°C, more preferably 90°C to 110°C, and more preferably 100°C; after drying, it is preferably ground and sieved; the mesh number of the sieved screen is preferably 80 to 400 meshes, more preferably 100 to 300 meshes, more preferably 150 to 250 meshes, and most preferably 200 meshes.
[0064] The composite solid electrolyte and the flexible polymer fiber are mixed in water and dried to obtain a composite solid electrolyte wrapped by the flexible polymer fiber; the flexible polymer fiber is preferably prepared according to the following steps: A1) the flexible polymer powder is mixed with the DMF solvent and allowed to stand to obtain a spinning solution; A2) the spinning solution is subjected to electrostatic spinning to obtain a flexible polymer fiber; the flexible polymer powder is preferably one or more of polyester, polyamide, polyvinyl alcohol and polyacrylonitrile; the molecular weight of the polyvinyl alcohol is preferably 120,000 to 150,000; the molecular weight of the polyester is preferably 20,000 to 30,000; the molecular weight of the polyamide is preferably 1,000 to 10,000; the molecular weight of the polyacrylonitrile is preferably 50,000 to 200,000; the mixing temperature is preferably 50°C The temperature of the spinning solution is preferably 5% to 15%, more preferably 6% to 12%, more preferably 7% to 11%, and most preferably 8% to 10%. The mixing time is preferably 1 to 3 hours, more preferably 1.5 to 2.5 hours, and more preferably 2 hours. The standing is preferably carried out at room temperature. The standing time is preferably 8 to 16 hours, more preferably 10 to 14 hours, more preferably 11 to 13 hours, and most preferably 12 hours. The mass concentration of the flexible polymer in the spinning solution is preferably 5% to 15%, more preferably 6% to 12%, more preferably 7% to 11%, and most preferably 8% to 10%. The flow rate of the electrospinning is preferably 0.2 to 0.5 mL / h, more preferably 0.3 to 0.4 mL / h, and more preferably 0.3mL / h; the humidity of the electrospinning is preferably 40% to 60%, more preferably 45% to 55%, and more preferably 50%; the receiving distance of the electrospinning is preferably 10 to 20cm, more preferably 14 to 18cm, more preferably 14 to 16cm, and most preferably 15cm; in some embodiments provided by the present invention, the receiving distance of the electrospinning is specifically 15cm, 12cm or 10cm; the voltage of the electrospinning is preferably 10 to 20kV, more preferably 10 to 18kV, more preferably 10 to 16kV, and most preferably 10 to 15kV; in some embodiments provided by the present invention, the voltage of the electrospinning is specifically 15kV or 10kV; the temperature of the electrospinning is preferably 20°C to 40°C , more preferably 20℃~30℃, more preferably 25℃; the mass ratio of the flexible polymer fiber to the composite solid electrolyte is preferably 1:(5~20), more preferably 1:(5~15), more preferably 1:(8~12), and most preferably 1:10; in some embodiments provided by the present invention, the mass ratio of the flexible polymer fiber to the composite solid electrolyte is specifically 1:10 or 1:5; the mixing time is preferably 6~12h, more preferably 6~10h, and more preferably 8h; the drying temperature is preferably 80℃~120℃, more preferably 90℃~110℃, and more preferably 100℃; the drying time is preferably 8~14h, more preferably 10~14h, more preferably 11~13h, and most preferably 12h. .
[0065] The composite solid electrolyte wrapped by the flexible polymer fiber is mixed with a perfluorocarboxylic acid and / or a perfluorocarboxylate in a solvent; the solvent is any solvent well known to those skilled in the art and is not particularly limited. In the present invention, water and / or an alcohol solvent is preferred, and deionized water, methanol, ethanol, acetone and isopropanol are more preferred. The mass ratio of the composite solid electrolyte wrapped by the flexible polymer fiber to the solvent is preferably 1:(1-10), more preferably 1:(2-5); the perfluorocarboxylic acid and / or the perfluorocarboxylate are preferably added in the form of a perfluorocarboxylic acid and / or perfluorocarboxylate solution; the mass concentration of the perfluorocarboxylic acid and / or the perfluorocarboxylate in the perfluorocarboxylic acid and / or perfluorocarboxylate solution is preferably 40% to 60%, more preferably 45% to 55%, and more preferably 50%; the mass ratio of the composite solid electrolyte wrapped by the flexible polymer fiber to the perfluorocarboxylic acid and / or the perfluorocarboxylate is preferably 50:1 to 5:1, more preferably 50:1 to 8:1, more preferably 40:1 to 8:1, more preferably 30:1 to 8:1, and most preferably 20:1 to 8:1; in some embodiments provided by the present invention, the mass ratio of the composite solid electrolyte wrapped by the flexible polymer fiber to the perfluorocarboxylic acid and / or the perfluorocarboxylate is specifically 20:1, 8:1, and the mixing is preferably carried out at room temperature; the mixing time is preferably 2 to 6 hours, more preferably 3 to 5 hours, and more preferably 4 hours.
[0066] After mixing, drying is performed to obtain a modified composite solid electrolyte; the drying temperature is preferably 80°C to 120°C, more preferably 90°C to 110°C, and more preferably 100°C; after drying, grinding and sieving are preferably performed to obtain a modified composite solid electrolyte; the mesh number of the sieving is preferably 80 to 400 meshes, more preferably 100 to 300 meshes, more preferably 150 to 250 meshes, and most preferably 200 meshes.
[0067] The present invention also provides a battery, comprising the modified composite solid electrolyte.
[0068] Specifically, the battery includes a positive electrode, a separator and a negative electrode; the positive electrode includes the above-mentioned modified composite solid electrolyte; the negative electrode includes the above-mentioned modified composite solid electrolyte.
[0069] Further specifically, the positive electrode includes a positive electrode active layer; the mass concentration of the modified composite solid electrolyte in the positive electrode active layer is 0.5wt% to 10wt%, more preferably 0.5wt% to 8wt%, more preferably 0.5wt% to 7wt%, more preferably 0.5wt% to 6wt%, and most preferably 0.5wt% to 5wt%; in some embodiments provided by the present invention, the mass concentration of the modified composite solid electrolyte in the positive electrode active layer is specifically 2wt%, 1wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt% or 8wt%; the particle size of the modified composite solid electrolyte is preferably 50 to 600nm, more preferably 100 to 500nm, more preferably 100 to 400nm, more preferably 150 to 300nm, and most preferably 200nm; the positive electrode active layer also includes a positive electrode active material, a positive electrode conductive agent and a positive electrode binder; the mass ratio of the positive electrode active material, the positive electrode conductive agent and the positive electrode binder is preferably (80 ~89):(1~5):(1~5), more preferably (82~89):(3~5):(3~5), and even more preferably (82~89):5:5; the positive electrode active material can be a positive electrode active material well known to those skilled in the art, without any special restrictions. In the present invention, it is preferably one or more of nickel cobalt manganese oxide positive electrode material (NCM), lithium cobalt oxide (LCO) and lithium iron phosphate (LFP); the positive electrode conductive agent can be a conductive agent well known to those skilled in the art, without any special restrictions. In the present invention, it is preferably one or more of carbon black SUPER-P, conductive graphite KS-6, carbon nanofibers, carbon nanotubes CNT, acetylene black, graphene and ketjen carbon; the positive electrode binder can be a binder well known to those skilled in the art, without any special restrictions. In the present invention, it is preferably one or more of polyvinylidene fluoride, polyacrylamide, polymethyl methacrylate-butyl acrylate, ethylene-vinyl acetate copolymer, polyvinyl acetate, polyurethane and polytetrafluoroethylene.
[0070] Further specifically, the negative electrode includes a negative electrode active layer; the mass concentration of the modified composite solid electrolyte in the negative electrode active layer is 0.5wt% to 10wt%, more preferably 0.5wt% to 8wt%, more preferably 0.5wt% to 7wt%, more preferably 0.5wt% to 6wt%, and most preferably 0.5wt% to 5wt%; in some embodiments provided by the present invention, the mass concentration of the modified composite solid electrolyte in the negative electrode active layer is specifically 2wt%, 1wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt% or 8wt%; the particle size of the modified composite solid electrolyte is preferably 50 to 600nm, more preferably 100 to 500nm, more preferably 200 to 400nm, more preferably 250 to 300nm, and most preferably 300nm; the negative electrode active layer also includes a negative electrode active material, a negative electrode conductive agent and a negative electrode binder; the negative electrode active material, the negative electrode conductive agent and the negative electrode binder The mass ratio of is preferably (80-89):(1-5):(1-5), more preferably (82-89):(3-5):(3-5), and further preferably (82-89):5:5; the negative electrode active material can be any negative electrode active material well known to those skilled in the art, without any special restrictions, and in the present invention, it is preferably one or more of artificial graphite (AG), SiO and SiC; the negative electrode conductive agent can be any conductive agent well known to those skilled in the art, without any special restrictions, and in the present invention, it is preferably one or more of carbon black SUPER-P, conductive graphite KS-6, carbon nanofibers, carbon nanotubes CNT, acetylene black, graphene and Ketjen carbon; the negative electrode binder can be any binder well known to those skilled in the art, without any special restrictions, and in the present invention, it is preferably one or more of polyvinylidene fluoride, polyacrylamide, polymethyl methacrylate-butyl acrylate, ethylene-vinyl acetate copolymer, polyvinyl acetate, polyurethane and polytetrafluoroethylene.
[0071] The present invention also provides a method for preparing a battery, comprising the following steps: B1) mixing and grinding the above-mentioned modified composite solid electrolyte with a solvent to obtain a modified composite solid electrolyte slurry; B2) mixing the modified composite solid electrolyte slurry, a positive electrode active material, a positive electrode conductive agent and a positive electrode binder to obtain a positive electrode slurry; mixing the modified composite solid electrolyte slurry, a negative electrode active material, a conductive agent and a binder to obtain a negative electrode slurry; B3) coating the positive electrode slurry on a positive electrode collector to obtain a positive electrode sheet; coating the negative electrode slurry on a negative electrode collector to obtain a negative electrode sheet; assembling the positive electrode sheet, a separator and a negative electrode sheet to obtain a battery.
[0072] Among them, the present invention has no special restrictions on the sources of all raw materials as long as they are commercially available. The modified composite solid electrolyte, positive electrode active material, positive electrode conductive agent, positive electrode binder, negative electrode active material, negative electrode conductive agent and negative electrode binder are all as described above and will not be repeated here.
[0073] According to the present invention, the solvent in the modified composite solid electrolyte slurry can be a solvent well known to those skilled in the art without any special restrictions. In the present invention, it is preferably one or more of water, ethanol, isopropanol and N-methylpyrrolidone (NMP); the mass ratio of the modified composite solid electrolyte to the solvent is preferably 1: (10-30), more preferably 1: (15-25), and more preferably 1: 20.
[0074] In order to further illustrate the present invention, a modified composite solid electrolyte, a preparation method thereof and applications provided by the present invention are described in detail below in conjunction with embodiments.
[0075] The reagents used in the following examples are all commercially available.
[0076] Example 1
[0077] 1.1 Preparation of LASTPF materials
[0078] Weigh 54.31 g of lithium carbonate, 20.39 g of aluminum oxide, 127.79 g of titanium dioxide, 333.58 g of diammonium phosphate, 3.70 g of ammonium fluoride, and 6.01 g of silicon dioxide, mix the precursors, and then sinter the precursors at a sintering temperature of 900° C. for 16 hours.
[0079] The above powder was dispersed in anhydrous ethanol solvent by planetary ball milling process, and an appropriate amount of grinding solution (grinding solvent to material ratio was 3:1) was added and ground for 3 h, wherein the ball to material ratio was 5.
[0080] 1.2 After grinding, the slurry is dried at 100° C. After drying, a powder agglomerated into a block is obtained, and the powder is ground through a 200-mesh sieve using a mortar to obtain LASTPF powder.
[0081] 1.3 Preparation of polyvinyl alcohol fibers by electrospinning
[0082] 10g of polyvinyl alcohol powder (molecular weight 150,000) was added to 100g of DMF solvent, stirred at 80°C for 2h until it became a uniform polymer solution, and placed at room temperature for 12h. The electrospinning machine was used for spinning, and the polymer concentration was set to 8%, the spinning flow rate was 0.3mL / h, the humidity was 50%, the receiving distance was 15cm, the voltage was 15kV, the cabinet temperature was 25°C, and the prepared polyvinyl alcohol (PVAs) fibers were collected using a roller.
[0083] 1.4 Take 5 g of the PVAs fiber prepared above and 50 g of LASTPF, mix them thoroughly in 100 g of water and stir for 8 h, and dry them in an oven at 100 °C for 12 h to obtain a polyvinyl alcohol fiber-coated solid electrolyte, which is recorded as PVAs@LASTPF.
[0084] 1.5 Preparation of PFCA-PVAs@LASTPF by hydrophobic treatment
[0085] The above PVAs@LASTPF was subjected to hydrophobic treatment: 50g of the above PVAs@LASTPF powder was dissolved in 100g of ethanol solvent, 5g of perfluorooctanoic acid (PFOA) solution (solution concentration was 50%) was added, and the mixture was stirred at room temperature for 4h, and perfluorooctanoic acid (PFOA) was grafted on the surface of the PVAs polymer layer to obtain a solid electrolyte wrapped in a polymer layer with hydrophobic properties, which was recorded as PFOA-PVAs@LASTPF. The above slurry was dried at a temperature of 100°C, and a powder agglomerated into a block was obtained after drying. The above powder was ground with a mortar through a 200-mesh screen to obtain a modified composite solid electrolyte recorded as PFOA-PVAs@LASTPF.
[0086] The modified composite solid electrolyte obtained in Example 1 was analyzed by X-ray diffraction, and its XRD pattern was as follows: Figure 2 shown.
[0087] 1.6 Testing the ionic conductivity and electronic conductivity of PFOA-PVAs@LASTPF
[0088] Take 3g of the above PFOA-PVAs@LASTPF material and use a mold with a diameter of 10mm. Apply a pressure of 10MPa in a desktop powder tablet press. After holding the pressure for 15min, demold the PFOA-PVAs@LASTPF sheet. Place the above sheet in a sintering furnace, heat it to 1000℃ at 2℃, and keep it warm for 12h to obtain a PFOA-PVAs@LASTPF ceramic sheet. Use 1000-mesh sandpaper moistened with alcohol to gently polish the surface of the above ceramic sheet according to the cross-cross method to remove surface impurities and ensure that the thickness of the electrolyte is uniform at all positions. Use a vernier caliper to measure the thickness L1 of the ceramic sheet, use an ion sputtering instrument to evaporate gold blocking electrodes, and use AC impedance to test the ionic conductivity of PFOA-PVAs@LASTPF, recorded as σ1.
[0089] Based on the principle of testing the electronic conductivity of powder by the four-probe method, the electronic conductivity of PFOA-PVAs@LASTPF was tested. 10g of the above PFOA-PVAs@LASTPF material was added to the powder resistance tester for testing. The electronic conductivity of the sample was tested at a pressure of 200MPa, which was recorded as ρ1.
[0090] 1.7 Positive electrode blending
[0091] The PFOA-PVAs@LASTPF powder is added with a certain amount of ground NMP solvent (mass ratio of 1:20) to obtain the PFOA-PVAs@LASTPF slurry. The particle size range of the powder is controlled at 200nm, and the positive electrode active material NCM811, the conductive agent carbon black SUPER-P, and the binder polyacrylamide are selected and dispersed in the NMP slurry of PFOA-PVAs@LASTPF, wherein the mass ratio of NCM811, carbon black SUPER-P, polyacrylamide and PFOA-PVAs@LASTPF is 88:5:5:2, and the mixture is stirred and mixed to prepare the positive electrode slurry.
[0092] 1.8 Negative electrode blending
[0093] The PFOA-PVAs@LASTPF powder is added with a certain amount of grinding NMP solvent (mass ratio of 1:20) to obtain PFOA-PVAs@LASTPF slurry. The particle size range of the powder is controlled at 300nm, and the negative electrode active material artificial graphite (AG), conductive agent carbon black SUPER-P, and binder polyacrylamide are selected and dispersed in the NMP slurry of PFOA-PVAs@LASTPF, wherein the mass ratio of AG, carbon black SUPER-P, polyacrylamide, and PFOA-PVAs@LASTPF is 88:5:5:2, and stirred and mixed to prepare the negative electrode slurry.
[0094] 1.9 Testing the electrochemical performance of the battery after blending
[0095] The above materials were prepared into CR2032 button batteries, wherein the separator used was a PE separator with a thickness of 11 μm, and the surface density of the positive electrode active material NCM811 was 316.1 g / cm 2 , compacted density is 3.2g / cm 3 The surface density of the negative electrode active material AG used is 200 g / cm 2 , compacted density is 1.6g / cm 3 ; The active materials of both the negative and positive electrodes have been mixed with PFOA-PVAs@LASTPF.
[0096] The assembled button cell was subjected to constant current charge and discharge tests on the battery test system, with a voltage range of 3 to 4.2 V and a rate of 0.05C. The results are shown in Table 1.
[0097] Example 2
[0098] 2.1 Preparation of LASTPCl materials
[0099] Weigh 54.31 g of lithium carbonate, 20.39 g of aluminum oxide, 127.79 g of titanium dioxide, 333.58 g of diammonium hydrogen phosphate, 5.35 g of ammonium chloride, and 4.41 g of silicon oxide, mix the precursors, and then sinter the precursors at a sintering temperature of 850° C. for 12 h.
[0100] The above powder was dispersed in anhydrous ethanol solvent by planetary ball milling process, and an appropriate amount of grinding solution (grinding solvent to material ratio was 3:1) was added and ground for 4 hours, wherein the ball to material ratio was 10.
[0101] 2.2 After grinding, the slurry is dried at 90°C. After drying, a powder agglomerated into a block is obtained, and the powder is ground with a mortar and passed through a 100-mesh sieve to obtain LASTPCl powder.
[0102] 2.3 Preparation of polyester fibers by electrospinning
[0103] Add 5g of polyester powder (molecular weight 20,000) to 100g of DMF solvent, stir at 70℃ for 1h until it becomes a uniform polymer solution, and place it at room temperature for 10h. Use an electrospinning machine for spinning, set the polymer concentration to 7%, the spinning flow rate to 0.2mL / h, the humidity to 40%, the receiving distance to 12cm, the voltage to 10kV, the cabinet temperature to 25℃, and use a roller to collect the prepared polyester (PETs) fibers.
[0104] 2.4 Take 10 g of the PETs fiber prepared above and 50 g of LASTPCl in 100 g of aqueous solution, mix them thoroughly and stir for 6 h, and dry them in an oven at 80 °C for 10 h to obtain polyester fiber-coated PETs@LASTPCl.
[0105] 2.5 Preparation of PFHPA-PETs@LASTPCl by hydrophobic treatment
[0106] The PETs@LASTPCl is subjected to a hydrophobic treatment. 50 g of the PETs@LASTPCl powder is dissolved in 100 g of ethanol solvent, and 5 g of perfluoroheptanoic acid (PFHPA) solution (solution concentration is 50%) is added. Stir at room temperature for 2 hours to graft perfluoroheptanoic acid (PFHPA) on the surface of the PETs polymer layer. PFHPA-PETs@LASTPCl wrapped in a polymer layer with hydrophobic properties is obtained. The slurry is dried at a temperature of 100°C. After drying, a powder agglomerated into a block is obtained. The powder is ground into a 100-mesh sieve using a mortar to obtain PFHPA-PETs@LASTPCl powder.
[0107] 2.6 Testing the ionic and electronic conductivity of PFHPA-PETs@LASTPCl
[0108] Take 2g of the above PFHPA-PETs@LASTPCl material and use a mold with a diameter of 10mm. Apply a pressure of 10MPa in a desktop powder tablet press. After holding the pressure for 10min, demold and obtain a PFHPA-PETs@LASTPCl sheet. Place the above sheet in a sintering furnace, heat it to 1000℃ at 2℃, and keep it warm for 12h. You can get a PFHPA-PETs@LASTPCl ceramic sheet. Use 1000-mesh sandpaper moistened with alcohol to gently polish the surface of the above ceramic sheet according to the cross-cross method to remove surface impurities and ensure that the thickness of the electrolyte is uniform at all positions. Use a vernier caliper to measure the thickness L2 of the ceramic sheet, use an ion sputtering instrument to evaporate the gold blocking electrode, and use AC impedance to test the ionic conductivity of PFHPA-PETs@LASTPCl, recorded as σ2.
[0109] Based on the principle of testing the electronic conductivity of powder by the four-probe method, the electronic conductivity of PFHPA-PETs@LASTPCl was tested. 10g of the above PFHPA-PETs@LASTPCl material was added to the powder resistance tester for testing. The electronic conductivity of the sample was tested at a pressure of 200MPa, which was recorded as ρ2.
[0110] 2.7 Positive Electrode Blending
[0111] The above PFHPA-PETs@LASTPCl powder is added with a certain amount of ground NMP solvent (mass ratio of 1:20) to obtain PFHPA-PETs@LASTPCl slurry. The particle size range of the powder is controlled at 200nm, and the positive electrode active material NCM811, the conductive agent carbon black SUPER-P, and the binder polyacrylamide are selected and dispersed in the NMP slurry of PFHPA-PETs@LASTPCl, wherein the mass ratio of NCM811, carbon black SUPER-P, polyacrylamide and PFHPA-PETs@LASTPCl is 89:5:5:1, and stirred and mixed to prepare the positive electrode slurry.
[0112] 2.8 Negative electrode blending
[0113] The above PFHPA-PETs@LASTPCl powder is added with a certain amount of ground NMP solvent (mass ratio of 1:20) to obtain PFHPA-PETs@LASTPCl slurry. The particle size range of the powder is controlled at 200nm, and the negative electrode active material AG, the conductive agent carbon black SUPER-P, and the binder polyacrylamide are selected and dispersed in the NMP slurry of PFHPA-PETs@LASTPCl, wherein the mass ratio of AG, carbon black SUPER-P, polyacrylamide and PFHPA-PETs@LASTPCl is 89:5:5:1, and stirred and mixed to prepare the negative electrode slurry.
[0114] 2.9 Testing the electrochemical performance of the battery after blending
[0115] The above materials were prepared into CR2032 button batteries. The separator used was a PE separator with a thickness of 11 μm, and the surface density of the positive electrode active material NCM811 was 316.1 g / cm 2 , compacted density is 3.2g / cm 3 The surface density of the negative electrode active material AG used is 200 g / cm 2 , compacted density is 1.6g / cm 3 ; The active materials of the negative electrode and the positive electrode have been mixed with PFHPA-PETs@LASTPCl.
[0116] The assembled button cell was subjected to constant current charge and discharge test on the battery test system, with a voltage range of 3 to 4.2 V and a rate of 0.05C.
[0117] Example 3
[0118] 3.1 Preparation of LAZTPBr materials
[0119] Weigh 50.43 g of lithium carbonate, 20.39 g of aluminum oxide, 127.79 g of titanium dioxide, 345.08 g of diammonium phosphate, 9.79 g of ammonium bromide, and 12.32 g of zirconium oxide, mix the precursors, and then sinter the precursors at a sintering temperature of 800° C. for 20 hours.
[0120] The above powder was dispersed in anhydrous ethanol solvent by planetary ball milling process, and an appropriate amount of grinding solution (grinding solvent to material ratio was 3:1) was added and ground for 3 h, wherein the ball to material ratio was 5.
[0121] 3.2 After grinding, the slurry is dried at 80°C. After drying, a powder agglomerated into a block is obtained, and the powder is ground with a mortar and passed through an 80-mesh sieve to obtain LAZTPBr powder.
[0122] 3.3 Preparation of polyamide fibers by electrospinning
[0123] 10g of polyamide (PA) powder (molecular weight 10000) was added to 100g of DMF solvent, stirred at 60°C for 3h until it became a uniform polymer solution, and placed at room temperature for 14h. The electrospinning machine was used for spinning, and the polymer concentration was set to 10%, the spinning flow rate was 0.5mL / h, the humidity was 60%, the receiving distance was 10cm, the voltage was 10kV, the cabinet temperature was 25°C, and the prepared polyamide (PA) fiber was collected using a roller.
[0124] 3.4 Take 5 g of the polyamide (PA) fiber prepared above and 50 g of LAZTPBr in 100 g of aqueous solution, mix them thoroughly and stir for 10 h, and dry them in an oven at 120°C for 14 h to obtain PA@LAZTPBr coated with polyvinyl alcohol fiber.
[0125] 3.5 Preparation of PFNA-PA@LAZTPBr by hydrophobic treatment
[0126] The PA@LAZTPBr is subjected to hydrophobic treatment. 50g of the PA@LAZTPBr powder is dissolved in 100g of ethanol solvent, and 5g of perfluorononanoic acid (PFNA) solution (solution concentration is 50%) is added. Stir at room temperature for 6 hours to graft perfluorononanoic acid (PFNA) on the surface of the PA polymer layer. PFNA-PA@LAZTPBr wrapped in a hydrophobic polymer layer is obtained. The slurry is dried at a temperature of 100°C. After drying, a powder agglomerated into a block is obtained. The powder is ground into a mortar and passed through an 80-mesh sieve to obtain PFNA-PA@LAZTPBr powder.
[0127] 3.6 Testing the ionic and electronic conductivity of PFNA-PA@LAZTPBr
[0128] Take 3g of the above PFNA-PA@LAZTPBr and use a mold with a diameter of 10mm. Apply a pressure of 10MPa in a desktop powder tablet press. After holding the pressure for 15min, demold and obtain a thin sheet of PFNA-PA@LAZTPBr. Place the above thin sheet in a sintering furnace, heat it to 1000℃ at 2℃, and keep it warm for 12h. You can get a ceramic sheet of PFNA-PA@LAZTPBr. Use 1000-grit sandpaper moistened with alcohol to gently polish its surface according to the cross-cross method to remove surface impurities and ensure that the thickness of the electrolyte is uniform at all positions. Use a vernier caliper to measure the thickness L3 of the ceramic sheet, use an ion sputtering instrument to evaporate the gold blocking electrode, and use AC impedance to test the ionic conductivity of PFNA-PA@LAZTPBr, recorded as σ3.
[0129] Based on the principle of testing the electronic conductivity of powder by the four-probe method, the electronic conductivity of PFNA-PA@LAZTPBr was tested. 10g of the above PFNA-PA@LAZTPBr material was added to the powder resistance tester for testing. The electronic conductivity of the sample was tested at a pressure of 200MPa, which was recorded as ρ3.
[0130] 3.7 Positive Electrode Blending
[0131] The PFNA-PA@LAZTPBr powder is added with a certain amount of ground NMP solvent (mass ratio of 1:20) to obtain the PFNA-PA@LAZTPBr slurry. The particle size range of the powder is controlled at 600nm, and the positive electrode active material NCM811, the conductive agent carbon black SUPER-P, and the binder polyacrylamide are selected and dispersed in the NMP slurry of PFNA-PA@LAZTPBr, wherein the mass ratio of NCM811, carbon black SUPER-P, polyacrylamide, and PFNA-PA@LAZTPBr is 87:5:5:3, and stirred and mixed to prepare the positive electrode slurry.
[0132] 3.8 Negative electrode blending
[0133] The PFNA-PA@LAZTPBr powder is added with a certain amount of ground NMP solvent (mass ratio of 1:20) to obtain the PFNA-PA@LAZTPBr slurry. The particle size range of the powder is controlled at 600nm, and the negative electrode active material AG, the conductive agent carbon black SUPER-P, and the binder polyacrylamide are selected and dispersed in the NMP slurry of PFNA-PA@LAZTPBr, wherein the mass ratio of AG, carbon black SUPER-P, polyacrylamide, and PFNA-PA@LAZTPBr is 87:5:5:3, and stirred and mixed to prepare the negative electrode slurry.
[0134] 3.9 Testing the electrochemical performance of the battery after blending
[0135] The above materials were prepared into CR2032 button batteries. The separator used was a PE separator with a thickness of 11 μm, and the surface density of the positive electrode active material NCM811 was 316.1 g / cm 2 , compacted density is 3.2g / cm 3 The surface density of the negative electrode active material AG used is 200 g / cm 2 , compacted density is 1.6g / cm 3 ; The active materials of both the negative and positive electrodes have been mixed with PFNA-PA@LAZTPBr.
[0136] The assembled button cell was subjected to constant current charge and discharge test on the battery test system, with a voltage range of 3 to 4.2 V and a rate of 0.05C.
[0137] Example 4
[0138] 4.1 Preparation of LANTPI materials
[0139] Weigh 50.43 g of lithium carbonate, 20.39 g of aluminum oxide, 127.79 g of titanium dioxide, 26.58 g of niobium pentoxide, 333.58 g of ammonium dihydrogen phosphate, and 14.49 g of ammonium iodide, and after the precursors are mixed, sinter the precursors at a sintering temperature of 950° C. for 24 hours.
[0140] The above powder was dispersed in anhydrous ethanol solvent by planetary ball milling process, and an appropriate amount of grinding solution (grinding solvent to material ratio was 3:1) was added and ground for 3 h, wherein the ball to material ratio was 5.
[0141] 4.2 After grinding, the slurry is dried at 100°C. After drying, a powder agglomerated into a block is obtained, and the powder is ground with a mortar and passed through a 200-mesh sieve to obtain LANTPI powder.
[0142] 4.3 Preparation of polyacrylonitrile fibers by electrospinning
[0143] Add 10g of polyacrylonitrile powder (molecular weight 50,000) to 100g of DMF solvent, stir at 80℃ for 2h until it becomes a uniform polymer solution, and place at room temperature for 12h. Use an electrospinning machine for spinning, set the polymer concentration to 8%, the spinning flow rate to 0.3ml / h, the humidity to 50%, the receiving distance to 15cm, the voltage to 15kV, the cabinet temperature to 25℃, and use a roller to collect the prepared polyacrylonitrile (PAN) fiber.
[0144] 4.4 Take 5 g of the PAN fiber prepared above and 50 g of LANTPI, mix them thoroughly in an aqueous solution and stir for 8 h, and dry them in an oven at 100°C for 12 h to obtain PAN@LANTPI coated with polyvinyl alcohol fiber.
[0145] 4.5 Preparation of PFHA-PAN@LANTPI by hydrophobic treatment
[0146] The above PAN@LANTPI was treated with hydrophobicity. 50g of the above PAN@LANTPI powder was dissolved in 100g of water, and 5g of perfluorohexanoic acid (PFHA) solution (solution concentration was 50%) was added. The mixture was stirred at room temperature for 4 hours to graft perfluorohexanoic acid (PFHA) on the surface of the PAN polymer layer. PFHA-PAN@LANTPI wrapped in a polymer layer with hydrophobic properties was obtained. The above slurry was dried at a temperature of 100°C. After drying, a powder agglomerated into a block was obtained. The above powder was ground with a mortar and passed through a 200-mesh sieve to obtain PFHA-PAN@LANTPI powder.
[0147] 4.6 Testing the ionic and electronic conductivity of PFHA-PAN@LANTPI
[0148] Take 3g of the above PFHA-PAN@LANTPI material and use a mold with a diameter of 10mm. Apply a pressure of 10MPa in a desktop powder tablet press. After holding the pressure for 15min, demold and obtain a PFHA-PAN@LANTPI sheet. Place the above sheet in a sintering furnace, heat it to 1000℃ at 2℃, and keep it warm for 12h. You can get a PFHA-PAN@LANTPI ceramic sheet. Use 1000-grit sandpaper moistened with alcohol to gently polish the surface of the above ceramic sheet according to the cross-cross method to remove surface impurities and ensure that the thickness of the electrolyte is uniform at all positions. Use a vernier caliper to measure the thickness L4 of the ceramic sheet, use an ion sputtering instrument to evaporate the gold blocking electrode, and use AC impedance to test the ionic conductivity of PFHA-PAN@LANTPI, recorded as σ4.
[0149] Based on the principle of testing the electronic conductivity of powder by the four-probe method, the electronic conductivity of PFHA-PAN@LANTPI was tested. 10g of the above PFHA-PAN@LANTPI material was added to the powder resistance tester for testing. The electronic conductivity of the sample was tested at a pressure of 200MPa, which was recorded as ρ4.
[0150] 4.7 Positive Electrode Blending
[0151] The PFHA-PAN@LANTPI powder is added with a certain amount of ground NMP solvent (mass ratio of 1:20) to obtain a PFHA-PAN@LANTPI slurry. The particle size range of the powder is controlled at 200nm, and the positive electrode active material NCM811, the conductive agent carbon black SUPER-P, and the binder polyacrylamide are selected and dispersed in the NMP slurry of PFHA-PAN@LANTPI, wherein the mass ratio of NCM811, carbon black SUPER-P, polyacrylamide, and PFHA-PAN@LANTPI is 86:5:5:4, and stirred and mixed to prepare the positive electrode slurry.
[0152] 4.8 Negative Electrode Blending
[0153] The PFHA-PAN@LANTPI powder is added with a certain amount of ground NMP solvent (mass ratio of 1:20) to obtain PFHA-PAN@LANTPI slurry. The particle size range of the powder is controlled at 300nm, and the negative electrode active material AG, the conductive agent carbon black SUPER-P, and the binder polyacrylamide are selected and dispersed in the NMP slurry of PFHA-PAN@LANTPI, wherein the mass ratio of AG, carbon black SUPER-P, polyacrylamide, and PFHA-PAN@LANTPI is 86:5:5:4, and stirred and mixed to prepare the negative electrode slurry.
[0154] 4.9 Testing the electrochemical performance of the battery after blending
[0155] The above materials were prepared into CR2032 button batteries. The separator used was a PE separator with a thickness of 11 μm, and the surface density of the positive electrode active material NCM811 was 316.1 g / cm 2 , compacted density is 3.2g / cm 3 The surface density of the negative electrode active material AG used is 200 g / cm 2 , compacted density is 1.6g / cm 3 ; The active materials of both the negative and positive electrodes have been mixed with PFHA-PAN@LANTPI.
[0156] The assembled button cell was subjected to constant current charge and discharge test on the battery test system, with a voltage range of 3 to 4.2 V and a rate of 0.05C.
[0157] Example 5
[0158] 5.1 Preparation of LATTPCl materials
[0159] Weigh 50.43 g of lithium carbonate, 20.39 g of aluminum oxide, 127.79 g of titanium dioxide, 26.09 g of tantalum pentoxide, 333.58 g of diammonium phosphate, and 7.46 g of potassium chloride, mix the precursors, and then sinter the precursors at a sintering temperature of 1000° C. for 12 hours.
[0160] The above powder was dispersed in anhydrous ethanol solvent by planetary ball milling process, and an appropriate amount of grinding solution (grinding solvent to material ratio was 3:1) was added and ground for 3 h, wherein the ball to material ratio was 5.
[0161] 5.2 After grinding, the slurry is dried at 100°C. After drying, a powder agglomerated into a block is obtained, and the powder is ground with a mortar and passed through a 200-mesh sieve. The powder of LATTPCl can be obtained.
[0162] 5.3 Preparation of polyvinyl alcohol fibers by electrospinning
[0163] 10g of polyvinyl alcohol powder (molecular weight 150,000) was added to 100g of DMF solvent, stirred at 80°C for 2h until it became a uniform polymer solution, and placed at room temperature for 12h. The electrospinning machine was used for spinning, and the polymer concentration was set to 8%, the spinning flow rate was 0.3ml / h, the humidity was 50%, the receiving distance was 15cm, the voltage was 15kV, the cabinet temperature was 25°C, and the prepared polyvinyl alcohol (PVAs) fibers were collected using a roller.
[0164] 5.4 Take 5 g of the PVA fiber prepared above and 50 g of LAMTPN, mix them thoroughly in an aqueous solution and stir for 8 h, and dry them in an oven at 100 °C for 12 h to obtain PVA fiber-coated PVA@LATTPCl.
[0165] 5.5 Preparation of PFVA-PVAs@LATTPCl by hydrophobic treatment
[0166] The PVAs@LATTPCl is subjected to a hydrophobic treatment. 50 g of the PVAs@LATTPCl powder is dissolved in 100 g of ethanol solvent, and 5 g of perfluoropentanoic acid (PFVA) solution (solution concentration is 50%) is added. Stir at room temperature for 4 hours to graft perfluoropentanoic acid (PFVA) on the surface of the PVA polymer layer. PFVA-PVAs@LATTPCl wrapped in a hydrophobic polymer layer is obtained. The slurry is dried at a temperature of 100°C. After drying, a powder agglomerated into a block is obtained. The powder is ground into a mortar and passed through a 200-mesh sieve to obtain the PFVA-PVAs@LATTPCl powder.
[0167] 5.6 Testing the ionic and electronic conductivity of PFVA-PVAs@LATTPCl
[0168] Take 3g of the above PFVA-PVAs@LATTPCl material and use a mold with a diameter of 10mm. Apply a pressure of 10MPa in a desktop powder tablet press. After holding the pressure for 15min, demold and obtain a PFVA-PVAs@LATTPCl sheet. Place the above sheet in a sintering furnace, heat it to 1000℃ at 2℃, and keep it warm for 12h. You can get a PFVA-PVAs@LATTPCl ceramic sheet. Use 1000-mesh sandpaper moistened with alcohol to gently polish the surface of the above ceramic sheet according to the cross-cross method to remove surface impurities and ensure that the thickness of the electrolyte is uniform at all positions. Use a vernier caliper to measure the thickness of the ceramic sheet L5, use an ion sputtering instrument to evaporate the gold blocking electrode, and use AC impedance to test the ionic conductivity of PFVA-PVAs@LATTPCl, recorded as σ5.
[0169] Based on the principle of testing the electronic conductivity of powder by the four-probe method, the electronic conductivity of PFVA-PVAs@LATTPCl was tested. 10g of the above PFVA-PVAs@LATTPCl material was added to the powder resistance tester for testing. The electronic conductivity of the sample was tested at a pressure of 200MPa, which was recorded as ρ5.
[0170] 5.7 Positive Electrode Blending
[0171] The above PFVA-PVAs@LATTPCl powder is added with a certain amount of ground NMP solvent (mass ratio of 1:20) to obtain PFVA-PVAs@LATTPCl slurry. The particle size range of the powder is controlled at 200nm, and the positive electrode active material NCM811, the conductive agent carbon black SUPER-P, and the binder polyacrylamide are selected and dispersed in the NMP slurry of PFVA-PVAs@LATTPCl, wherein the mass ratio of NCM811, carbon black SUPER-P, polyacrylamide, and PFVA-PVAs@LATTPCl is 85:5:5:5, and stirred and mixed to prepare the positive electrode slurry.
[0172] 5.8 Negative Electrode Blending
[0173] The above PFVA-PVAs@LATTPCl powder is added with a certain amount of ground NMP solvent (mass ratio of 1:20) to obtain PFVA-PVAs@LATTPCl slurry. The particle size range of the powder is controlled at 300nm, and the negative electrode active material AG, the conductive agent carbon black SUPER-P, and the binder polyacrylamide are selected and dispersed in the NMP slurry of PFVA-PVAs@LATTPCl, wherein the mass ratio of AG, carbon black SUPER-P, polyacrylamide, and PFVA-PVAs@LATTPCl is 85:5:5:5, and stirred and mixed to prepare the negative electrode slurry.
[0174] 5.9 Testing the electrochemical performance of the battery after blending
[0175] The above materials were prepared into CR2032 button batteries. The separator used was a PE separator with a thickness of 11 μm, and the surface density of the positive electrode active material NCM811 was 316.1 g / cm 2 , compacted density is 3.2g / cm 3 The surface density of the negative electrode active material AG used is 200 g / cm 2 , compacted density is 1.6g / cm 3 ; The active materials of both the negative and positive electrodes have been mixed with PFVA-PVAs@LATTPCl.
[0176] The assembled button cell was subjected to constant current charge and discharge test on the battery test system, with a voltage range of 3 to 4.2 V and a rate of 0.05C.
[0177] Example 6
[0178] 6.1 Preparation of LASTPBr materials
[0179] Weigh 50.43 g of lithium carbonate, 20.39 g of aluminum oxide, 127.79 g of titanium dioxide, 333.58 g of diammonium phosphate, 6.01 g of silicon dioxide, and 11.90 g of potassium bromide, mix the precursors, and then sinter the precursors at a sintering temperature of 900° C. for 24 hours.
[0180] The above powder was dispersed in anhydrous ethanol solvent by planetary ball milling process, and an appropriate amount of grinding solution (grinding solvent to material ratio was 3:1) was added and ground for 3 h, wherein the ball to material ratio was 5.
[0181] 6.2 After grinding, the slurry is dried at 100°C. After drying, a powder agglomerated into a block is obtained, and the powder is ground with a mortar and passed through a 200-mesh sieve to obtain LASTPBr powder.
[0182] 6.3 Preparation of polyester fibers by electrospinning
[0183] Add 5g of polyester powder (molecular weight 30,000) to 100g of DMF solvent, stir at 70℃ for 1h until it becomes a uniform polymer solution, and place it at room temperature for 10h. Use an electrospinning machine for spinning, set the polymer concentration to 7%, the spinning flow rate to 0.2ml / h, the humidity to 40%, the receiving distance to 12cm, the voltage to 10kV, the cabinet temperature to 25℃, and use a roller to collect the prepared polyester (PETs) fibers.
[0184] 6.4 Take 5 g of the polyester (PET) fiber prepared above and 50 g of LASTPBr, mix them thoroughly in an aqueous solution and stir for 8 h, and dry them in an oven at 100°C for 12 h to obtain PET@LASTPBr coated with polyvinyl alcohol fiber.
[0185] 6.5 Preparation of HFBA-PET@LASTPBr by hydrophobic treatment
[0186] The above PET@LASTPBr is subjected to hydrophobic treatment. 50g of the above PET@LASTPBr powder is dissolved in 100g of ethanol solvent, and 5g of perfluorobutyric acid (HFBA) solution (solution concentration is 50%) is added. Stir at room temperature for 4 hours to graft perfluorobutyric acid (HFBA) on the surface of the PET polymer layer. HFBA-PET@LASTPBr wrapped in a polymer layer with hydrophobic properties is obtained. The above slurry is dried at a temperature of 100°C. After drying, a powder agglomerated into a block is obtained. The above powder is ground with a mortar and passed through a 200-mesh sieve to obtain the powder of HFBA-PET@LASTPBr.
[0187] 6.6 Testing the ionic and electronic conductivity of HFBA-PET@LASTPBr
[0188] Take 3g of the above HFBA-PET@LASTPBr material and use a mold with a diameter of 10mm. Apply a pressure of 10MPa in a desktop powder tablet press. After holding the pressure for 15min, demold and obtain a thin sheet of HFBA-PET@LASTPBr. Place the above thin sheet in a sintering furnace, heat it to 1000℃ at 2℃, and keep it warm for 12h. You can get a ceramic sheet of HFBA-PET@LASTPBr. Use 1000-mesh sandpaper moistened with alcohol to gently polish its surface according to the cross-cross method to remove surface impurities and ensure that the thickness of the electrolyte is uniform at all positions. Use a vernier caliper to measure the thickness L6 of the ceramic sheet, use an ion sputtering instrument to evaporate the gold blocking electrode, and use AC impedance to test the ionic conductivity of HFBA-PET@LASTPBr, recorded as σ6.
[0189] Based on the principle of testing the electronic conductivity of powder by the four-probe method, the electronic conductivity of HFBA-PET@LASTPBr was tested. 10g of the above HFBA-PET@LASTPBr material was added to the powder resistance tester for testing. The electronic conductivity of the sample was tested at a pressure of 200MPa and recorded as ρ6.
[0190] 6.7 Positive Electrode Blending
[0191] The above HFBA-PET@LASTPBr powder is added with a certain amount of ground NMP solvent (mass ratio of 1:20) to obtain HFBA-PET@LASTPBr slurry. The particle size range of the powder is controlled at 200nm, and the positive electrode active material NCM811, the conductive agent carbon black SUPER-P, and the binder polyacrylamide are selected and dispersed in the NMP slurry of HFBA-PET@LASTPBr, wherein the mass ratio of NCM811, carbon black SUPER-P, polyacrylamide, and HFBA-PET@LASTPBr is 84:5:5:6, and stirred and mixed to prepare the positive electrode slurry.
[0192] 6.8 Negative Electrode Blending
[0193] The above HFBA-PET@LASTPBr powder is added with a certain amount of ground NMP solvent (mass ratio of 1:20) to obtain HFBA-PET@LASTPBr slurry. The particle size range of the powder is controlled at 300nm, and the negative electrode active material AG, the conductive agent carbon black SUPER-P, and the binder polyacrylamide are selected and dispersed in the NMP slurry of HFBA-PET@LASTPBr, wherein the mass ratio of AG, carbon black SUPER-P, polyacrylamide, and HFBA-PET@LASTPBr is 84:5:5:6, and stirred and mixed to prepare the negative electrode slurry.
[0194] 6.9 Testing the electrochemical performance of the blended battery
[0195] The above materials were prepared into CR2032 button batteries. The separator used was a PE separator with a thickness of 11 μm, and the surface density of the positive electrode active material NCM811 was 316.1 g / cm 2 , compacted density is 3.2g / cm 3 The surface density of the negative electrode active material AG used is 200 g / cm 2 , compacted density is 1.6g / cm 3 ; The active materials of both the negative and positive electrodes have been mixed with HFBA-PET@LASTPBr.
[0196] The assembled button cell was subjected to constant current charge and discharge test on the battery test system, with a voltage range of 3 to 4.2 V and a rate of 0.05C.
[0197] Example 7
[0198] 7.1 Preparation of LASTPI Materials
[0199] Weigh 50.43 g of lithium carbonate, 20.39 g of aluminum oxide, 127.79 g of titanium dioxide, 333.58 g of diammonium phosphate, 6.01 g of silicon dioxide, and 16.60 g of potassium iodide, mix the precursors, and then sinter the precursors at a sintering temperature of 900° C. for 20 hours.
[0200] The above powder was dispersed in anhydrous ethanol solvent by planetary ball milling process, and an appropriate amount of grinding solution (grinding solvent to material ratio was 3:1) was added and ground for 3 h, wherein the ball to material ratio was 5.
[0201] 7.2 After grinding, the slurry is dried at 100°C. After drying, a powder agglomerated into a block is obtained, and the powder is ground with a mortar and passed through a 200-mesh sieve to obtain LASTPI powder.
[0202] 7.3 Preparation of polyamide fibers by electrospinning
[0203] 10g of polyamide (PA) powder (molecular weight 10000) was added to 100g of DMF solvent, stirred at 60℃ for 3h until it became a uniform polymer solution, and placed at room temperature for 14h. The electrospinning machine was used for spinning, and the polymer concentration was set to 8%, the spinning flow rate was 0.3ml / h, the humidity was 50%, the receiving distance was 15cm, the voltage was 15kV, the cabinet temperature was 25℃, and the prepared polyamide (PA) fiber was collected using a roller.
[0204] 7.4 Take 5 g of the polyamide (PA) fiber prepared above and 50 g of LASTPI, mix them thoroughly in an aqueous solution and stir for 8 h, and dry them in an oven at 100°C for 12 h to obtain PA@LASTPI coated with polyamide (PA) fiber.
[0205] 7.5 Preparation of PFDA-PA@LASTPI by hydrophobic treatment
[0206] The PA@LASTPI is subjected to hydrophobic treatment. 50g of the PA@LASTPI powder is dissolved in 100g of ethanol solvent, and 5g of perfluorodecanoic acid (PFDA) solution (solution concentration is 50%) is added. Stir at room temperature for 4 hours to graft perfluorodecanoic acid (PFDA) on the surface of the PA polymer layer. PFDA-PA@LASTPI wrapped in a polymer layer with hydrophobic properties is obtained. The slurry is dried at a temperature of 100°C. After drying, a powder agglomerated into a block is obtained. The powder is ground into a mortar and passed through a 200-mesh sieve to obtain the powder of PFDA-PA@LASTPI.
[0207] 7.6 Testing the ionic and electronic conductivity of PFDA-PA@LASTPI
[0208] Take 3g of the above PFDA-PA@LASTPI. Use a mold with a diameter of 10mm, apply a pressure of 10MPa in a desktop powder tablet press, and demold after holding the pressure for 15min to obtain a thin sheet of PFDA-PA@LASTPI. Place the above thin sheet in a sintering furnace, heat it to 1000℃ at 2℃, and keep it warm for 12h. You can get a ceramic sheet of PFDA-PA@LASTPI. Use 1000-grit sandpaper moistened with alcohol to gently polish the surface of the above ceramic sheet according to the cross-cross method to remove surface impurities and ensure that the thickness of the electrolyte is uniform at all positions. Use a vernier caliper to measure the thickness of the ceramic sheet L7, use an ion sputtering instrument to evaporate gold blocking electrodes, and use AC impedance to test the ionic conductivity of PFDA-PA@LASTPI, recorded as σ7.
[0209] Based on the principle of testing the electronic conductivity of powder by the four-probe method, the electronic conductivity of PFDA-PA@LASTPI was tested. 10g of the above PFDA-PA@LASTPI material was added to the powder resistance tester for testing. The electronic conductivity of the sample was tested at a pressure of 200MPa and recorded as ρ7.
[0210] 7.7 Positive Electrode Blending
[0211] Add a certain amount of ground NMP solvent (mass ratio of 1:20) to the above PFDA-PA@LASTPI powder to obtain PFDA-PA@LASTPI slurry. The particle size range of the powder is controlled at 200nm, and the positive electrode active material NCM811, the conductive agent carbon black SUPER-P, and the binder polyacrylamide are selected and dispersed in the NMP slurry of PFDA-PA@LASTPI, wherein the mass ratio of NCM811, carbon black SUPER-P, polyacrylamide, and HFBA-PET@LASTPBr is 83:5:5:7, and the mixture is stirred to prepare the positive electrode slurry.
[0212] 7.8 Negative Electrode Blending
[0213] The above PFDA-PA@LASTPI powder is added with a certain amount of ground NMP solvent (mass ratio of 1:20) to obtain the slurry of PFDA-PA@LASTPI. The particle size range of the powder is controlled at 300nm, and the negative electrode active material AG, the conductive agent carbon black SUPER-P, and the binder polyacrylamide are selected and dispersed in the NMP slurry of PFDA-PA@LASTPI, wherein the mass ratio of AG, carbon black SUPER-P, polyacrylamide, and PFDA-PA@LASTPI is 83:5:5:7, and stirred and mixed to prepare the negative electrode slurry.
[0214] 7.9 Testing the electrochemical performance of the blended battery
[0215] The above materials were prepared into CR2032 button batteries. The separator used was a PE separator with a thickness of 11 μm, and the surface density of the positive electrode active material NCM811 was 316.1 g / cm 2 , compacted density is 3.2g / cm 3 The surface density of the negative electrode active material AG used is 200 g / cm 2 , compacted density is 1.6g / cm 3 ; The active materials of both the negative and positive electrodes have been mixed with PFDA-PA@LASTPI.
[0216] The assembled button cell was subjected to constant current charge and discharge test on the battery test system, with a voltage range of 3 to 4.2 V and a rate of 0.05C.
[0217] Example 8
[0218] 8.1 Preparation of LASTPF Materials
[0219] Weigh 54.31 g of lithium carbonate, 20.39 g of aluminum oxide, 127.79 g of titanium dioxide, 6.01 g of silicon dioxide, 333.58 g of diammonium phosphate, and 3.90 g of calcium fluoride. After the precursors are mixed, sinter the precursors at a sintering temperature of 900° C. for 12 hours.
[0220] The above powder was dispersed in anhydrous ethanol solvent by planetary ball milling process, and an appropriate amount of grinding solution (grinding solvent to material ratio was 3:1) was added and ground for 3 h, wherein the ball to material ratio was 5.
[0221] 8.2 After grinding, the slurry is dried at 100°C. After drying, a powder agglomerated into a block is obtained. The powder is ground with a mortar and passed through a 200-mesh sieve. The powder of LASTPF is obtained.
[0222] 8.3 Preparation of polyacrylonitrile fibers by electrospinning
[0223] Add 10g of polyacrylonitrile powder (molecular weight 50,000) to 100g of DMF solvent, stir at 80℃ for 2h until it becomes a uniform polymer solution, and place at room temperature for 12h. Use an electrospinning machine for spinning, set the polymer concentration to 8%, the spinning flow rate to 0.3ml / h, the humidity to 50%, the receiving distance to 15cm, the voltage to 15kV, the cabinet temperature to 25℃, and use a roller to collect the prepared polyacrylonitrile (PAN) fiber.
[0224] 8.4 Take 5 g of the PAN fiber prepared above and 50 g of LASTPF, mix them thoroughly in an aqueous solution and stir for 8 h, and dry them in an oven at 100°C for 12 h to obtain PAN@LASTPF coated with polyvinyl alcohol fibers.
[0225] 8.5 Preparation of PFDOA-PAN@LASTPF by hydrophobic treatment
[0226] The PAN@LASTPF was subjected to a hydrophobic treatment. 50 g of the PAN@LASTPF powder was dissolved in 100 g of ethanol solvent, and 5 g of perfluorododecanoic acid (PFDOA) solution (solution concentration was 50%) was added. The mixture was stirred at room temperature for 4 hours to graft perfluorododecanoic acid (PFDOA) on the surface of the PAN polymer layer. PFDOA-PAN@LASTPF coated with a hydrophobic polymer layer was obtained. The slurry was dried at 100°C. After drying, a powder agglomerated into a block was obtained. The powder was ground into a mortar and passed through a 200-mesh sieve to obtain the powder of PFDOA-PAN@LASTPF.
[0227] 8.6 Testing the ionic and electronic conductivity of PFDOA-PAN@LASTPF
[0228] Take 3g of the above PFDOA-PAN@LASTPF material and use a mold with a diameter of 10mm. Apply a pressure of 10MPa in a desktop powder tablet press. After holding the pressure for 15min, demold and obtain a thin sheet of PFDOA-PAN@LASTPF. Place the above thin sheet in a sintering furnace, heat it to 1000℃ at 2℃, and keep it warm for 12h. You can get a ceramic sheet of PFDOA-PAN@LASTPF. Use 1000-grit sandpaper moistened with alcohol to gently polish the surface of the above ceramic sheet according to the cross-cross method to remove surface impurities and ensure that the thickness of the electrolyte is uniform at all positions. Use a vernier caliper to measure the thickness of the ceramic sheet L8, use an ion sputtering instrument to evaporate the gold blocking electrode, and use AC impedance to test the ionic conductivity of PFDOA-PAN@LASTPF, recorded as σ8.
[0229] Based on the principle of testing the electronic conductivity of powder by the four-probe method, the electronic conductivity of PFDOA-PAN@LASTPF was tested. 10g of the above PFDOA-PAN@LASTPF material was added to the powder resistance tester for testing. The electronic conductivity of the sample was tested at a pressure of 200MPa and recorded as ρ8.
[0230] 8.7 Positive Electrode Blending
[0231] Add a certain amount of ground NMP solvent (mass ratio of 1:20) to the above PFDOA-PAN@LASTPF powder to obtain a slurry of PFDOA-PAN@LASTPF. The particle size range of the powder is controlled at 200nm, and the positive electrode active material NCM811, the conductive agent carbon black SUPER-P, and the binder polyacrylamide are selected and dispersed in the NMP slurry of PFDOA-PAN@LASTPF, wherein the mass ratio of NCM811, carbon black SUPER-P, polyacrylamide, and PFDOA-PAN@LASTPF is 82:5:5:8, and the mixture is stirred and mixed to prepare the positive electrode slurry.
[0232] 8.8 Negative Electrode Blending
[0233] Add a certain amount of ground NMP solvent (mass ratio of 1:20) to the above PFDOA-PAN@LASTPF powder to obtain a slurry of PFDOA-PAN@LASTPF. The particle size range of the powder is controlled at 300nm, and the negative electrode active material AG, the conductive agent carbon black SUPER-P, and the binder polyacrylamide are selected and dispersed in the NMP slurry of PFDA-PA@LASTPI, wherein the mass ratio of AG, carbon black SUPER-P, polyacrylamide, and PFDA-PA@LASTPI is 82:5:5:8, and stirred and mixed to prepare the negative electrode slurry.
[0234] 8.9 Testing the electrochemical performance of the blended battery
[0235] The above materials were prepared into CR2032 button batteries. The separator used was a PE separator with a thickness of 11 μm, and the surface density of the positive electrode active material NCM811 was 316.1 g / cm 2 , compacted density is 3.2g / cm 3 The surface density of the negative electrode active material AG used is 200 g / cm 2 , compacted density is 1.6g / cm 3 ; The active materials of both the negative and positive electrodes have been mixed with PFDOA-PAN@LASTPF.
[0236] The assembled button cell was subjected to constant current charge and discharge test on the battery test system, with a voltage range of 3 to 4.2 V and a rate of 0.05C.
[0237] Comparative Example 1
[0238] 1.1 Preparation of LATP materials
[0239] Weigh 54.31 g of lithium carbonate, 20.39 g of aluminum oxide, 127.79 g of titanium dioxide, and 333.58 g of ammonium dihydrogen phosphate. After the precursors are mixed, sinter the precursors at a sintering temperature of 850° C. for 24 hours.
[0240] The above powder was dispersed in anhydrous ethanol solvent by planetary ball milling process, and an appropriate amount of grinding solution (grinding solvent to material ratio was 3:1) was added and ground for 3 h, wherein the ball to material ratio was 5.
[0241] 1.2 After grinding, the slurry is dried at 100°C. After drying, a powder agglomerated into a block is obtained, and the powder is ground with a mortar and passed through a 200-mesh sieve to obtain LATP powder.
[0242] The LATP powder obtained in Comparative Example 1 was analyzed by X-ray diffraction, and its XRD pattern was as follows: Figure 2 shown.
[0243] 1.3 Testing the ionic conductivity and electronic conductivity of LATP
[0244] Take 3g of the above LATP material. Use a mold with a diameter of 10mm, apply a pressure of 10MPa in a desktop powder tablet press, maintain the pressure for 15min, and then demold to obtain the LATP sheet. Place the above sheet in a sintering furnace, heat it to 1000℃ at 2℃, and keep it warm for 12h. You can get the LATP ceramic sheet. Use 1000-grit sandpaper moistened with alcohol to gently polish the surface of the above ceramic sheet according to the cross-cross method to remove surface impurities and ensure that the thickness of the electrolyte is uniform at all positions. Use a vernier caliper to measure the thickness Lv1 of the ceramic sheet, use an ion sputtering instrument to evaporate the gold blocking electrode, and use AC impedance to test the ionic conductivity of LATP, recorded as σv1.
[0245] Based on the principle of testing the electronic conductivity of powder by the four-probe method, the electronic conductivity of LATP was tested. 10g of the above LATP material was added to the powder resistance tester for testing. The electronic conductivity of the sample was tested at a pressure of 200MPa, which was recorded as ρv1.
[0246] 1.4 Positive electrode blending
[0247] The LATP powder is added with a certain amount of grinding NMP solvent (mass ratio of 1:20) to obtain LATP slurry. The particle size range of the powder is controlled to 200nm, and the positive electrode active material NCM811, the conductive agent carbon black SUPER-P, and the binder polyacrylamide are selected and dispersed in the LATP NMP slurry, wherein the mass ratio of NCM811, carbon black SUPER-P, polyacrylamide, and LATP is 85:5:5:5, and stirred and mixed to prepare the positive electrode slurry.
[0248] 1.5 Negative electrode blending
[0249] The LATP powder is added with a certain amount of grinding NMP solvent (mass ratio is 1:20) to obtain LATP slurry. The particle size range of the powder is controlled to 300nm, and the negative electrode active material AG, the conductive agent carbon black SUPER-P, and the binder polyacrylamide are selected and dispersed in the LATP NMP slurry, wherein the mass ratio of AG, carbon black SUPER-P, polyacrylamide, and LATP is 85:5:5:5, and stirred and mixed to prepare the negative electrode slurry.
[0250] 1.6 Testing the electrochemical performance of the battery after blending
[0251] The above materials were prepared into CR2032 button batteries. The separator used was a PE separator with a thickness of 11 μm, and the surface density of the positive electrode active material NCM811 was 316.1 g / cm 2 , compacted density is 3.2g / cm 3 The surface density of the negative electrode active material AG used is 200 g / cm 2 , compacted density is 1.6g / cm 3 ; The active materials of both the negative and positive electrodes have been mixed with LATP.
[0252] The assembled button cell was subjected to constant current charge and discharge test on the battery test system, with a voltage range of 3 to 4.2 V and a rate of 0.05C.
[0253] Comparative Example 2
[0254] 2.1 Preparation of LASTPF materials
[0255] Weigh 54.31 g of lithium carbonate, 20.39 g of aluminum oxide, 127.79 g of titanium dioxide, 333.58 g of diammonium hydrogen phosphate, 3.70 g of ammonium fluoride, and 6.01 g of silicon dioxide, mix the precursors, and then sinter the precursors at a sintering temperature of 950° C. for 24 hours.
[0256] The above powders were dispersed in anhydrous ethanol solvent by planetary ball milling process, and an appropriate amount of grinding solution was added and ground for 3 h, wherein the ball-to-material ratio was 5.
[0257] 2.2 After grinding, the slurry is dried at 100°C. After drying, a powder agglomerated into a block is obtained, and the powder is ground with a mortar and passed through a 200-mesh sieve to obtain LASTPF powder.
[0258] 2.3 Testing the ionic conductivity and electronic conductivity of LASTPF
[0259] Take 3g of the above LASTPF material. Use a mold with a diameter of 10mm, apply a pressure of 10MPa in a desktop powder tablet press, and demold after holding the pressure for 15min to obtain the LASTPF sheet. Place the above sheet in a sintering furnace, heat it to 1000℃ at 2℃, and keep it warm for 12h. You can get the LASTPF ceramic sheet. Use 1000-mesh sandpaper moistened with alcohol to gently polish the surface of the above ceramic sheet according to the cross-cross method to remove surface impurities and ensure that the thickness of the electrolyte is uniform at all positions. Use a vernier caliper to measure the thickness Lv2 of the ceramic sheet, use an ion sputtering instrument to evaporate the gold blocking electrode, and use AC impedance to test the ionic conductivity of LASTPF, recorded as σv2.
[0260] Based on the principle of testing the electronic conductivity of powder by the four-probe method, the electronic conductivity of LASTPF was tested. 10g of the above LASTPF material was added to the powder resistance tester for testing. The electronic conductivity of the sample was tested at a pressure of 200MPa, which was recorded as ρv2.
[0261] 2.4 Positive electrode blending
[0262] Add a certain amount of ground NMP solvent (mass ratio of 1:20) to the above LASTPF powder to obtain LASTPF slurry. The particle size range of the powder is controlled at 200nm, and the positive electrode active material NCM811, the conductive agent carbon black SUPER-P, and the binder polyacrylamide are selected and dispersed in the LASTPF NMP slurry, wherein the mass ratio of NCM811, carbon black SUPER-P, polyacrylamide, and LASTPF is 85:5:5:5, and stirred and mixed to prepare the positive electrode slurry.
[0263] 2.5 Negative electrode blending
[0264] Add a certain amount of grinding NMP solvent (mass ratio of 1:20) to the above LASTPF powder to obtain LASTPF slurry. The particle size range of the powder is controlled at 300nm, and the negative electrode active material AG, the conductive agent carbon black SUPER-P, and the binder polyacrylamide are selected and dispersed in the LASTPF NMP slurry, wherein the mass ratio of AG, carbon black SUPER-P, polyacrylamide, and LASTPF is 85:5:5:5, and stirred and mixed to prepare the negative electrode slurry.
[0265] 2.6 Testing the electrochemical performance of the battery after blending
[0266] The above materials were prepared into CR2032 button batteries. The separator used was a PE separator with a thickness of 11 μm, and the surface density of the positive electrode active material NCM811 was 316.1 g / cm 2 , compacted density is 3.2g / cm 3 The surface density of the negative electrode active material AG used is 200 g / cm 2 , compacted density is 1.6g / cm 3 ; The active materials of both the negative and positive electrodes have been mixed with LASTPF.
[0267] The assembled button cell was subjected to constant current charge and discharge test on the battery test system, with a voltage range of 3 to 4.2 V and a rate of 0.05C.
[0268] Comparative Example 3
[0269] 3.1 Preparation of LATP materials
[0270] Weigh 54.31 g of lithium carbonate, 20.39 g of aluminum oxide, 127.79 g of titanium dioxide, and 333.58 g of ammonium dihydrogen phosphate. After the precursors are mixed, sinter the precursors at a sintering temperature of 900° C. for 24 hours.
[0271] The above powder was dispersed in anhydrous ethanol solvent by planetary ball milling process, the ratio of anhydrous ethanol added to powder was 3:1, and ground for 5 hours, wherein the ball-to-material ratio was 15.
[0272] 3.2 After grinding, the slurry is dried at 100°C. After drying, a powder agglomerated into a block is obtained, and the powder is ground with a mortar and passed through a 200-mesh sieve to obtain LATP powder.
[0273] 3.3 Preparation of polyvinyl alcohol fibers by electrospinning
[0274] A certain amount of polyvinyl alcohol solution was added to the aqueous solution, stirred at 80°C for 2 hours until it became a uniform polymer solution, and placed at room temperature for 12 hours. The electrospinning machine was used for spinning, with the polymer concentration set to 8%, the spinning flow rate to 0.3 ml / h, the humidity to 50%, the receiving distance to 15 cm, the voltage to 15 kV, the cabinet temperature to 25°C, and the prepared polyvinyl alcohol (PVAs) fibers were collected using a roller.
[0275] 3.4 Take 5 g of the PVAs fiber prepared above and 50 g of LATP, mix them thoroughly in an aqueous solution and stir for 8 h, and dry them in an oven at 100°C for 12 h to obtain PVA fiber-coated PVAs@LATP.
[0276] 3.5 Testing the ionic and electronic conductivity of PVAs@LATP
[0277] Take 3g of the above PVAs@LATP material. Use a mold with a diameter of 12mm, apply a pressure of 10MPa in a desktop powder tablet press, maintain the pressure for 15min, and then demold to obtain a PVAs@LATP sheet. Place the above sheet in a sintering furnace, heat it to 1000℃ at 3℃, and keep it warm for 15h. You can get a PVAs@LATP ceramic sheet. Use 1000-grit sandpaper moistened with alcohol to gently polish the surface of the above ceramic sheet according to the cross-cross method to remove surface impurities and ensure that the thickness of the electrolyte is uniform at all positions. Use a vernier caliper to measure the thickness of the ceramic sheet Lv3, use an ion sputtering instrument to evaporate gold blocking electrodes, and use AC impedance to test the ionic conductivity of PVAs@LATP, recorded as σv3.
[0278] Based on the principle of testing the electronic conductivity of powder by the four-probe method, the electronic conductivity of PVAs@LATP was tested. 10g of the above PVAs@LATP material was added to the powder resistance tester for testing. The electronic conductivity of the sample was tested at a pressure of 200MPa, which was recorded as ρv3.
[0279] 3.6 Positive electrode blending
[0280] The above-mentioned PVAs@LATP powder is added with a certain amount of grinding NMP solvent (mass ratio of 1:20) to obtain PVAs@LATP slurry. The particle size range of the powder is controlled at 200nm, and the positive electrode active material NCM811, the conductive agent carbon black SUPER-P, and the binder polyacrylamide are selected and dispersed in the NMP slurry of PVAs@LATP, wherein the mass ratio of NCM811, carbon black SUPER-P, polyacrylamide, and PVAs@LATP is 85:5:5:5, and stirred and mixed to prepare the positive electrode slurry.
[0281] 3.7 Negative electrode blending
[0282] The above-mentioned PVAs@LATP powder is added with a certain amount of grinding NMP solvent (mass ratio of 1:20) to obtain PVAs@LATP slurry. The particle size range of the powder is controlled at 300nm, and the negative electrode active material AG, the conductive agent carbon black SUPER-P, and the binder polyacrylamide are selected and dispersed in the NMP slurry of PVAs@LATP, wherein the mass ratio of AG, carbon black SUPER-P, polyacrylamide, and PVAs@LATP is 85:5:5:5, and stirred and mixed to prepare the negative electrode slurry.
[0283] 3.8 Testing the electrochemical performance of the battery after blending
[0284] The above materials were prepared into CR2032 button batteries. The separator used was a PE separator with a thickness of 11 μm, and the surface density of the positive electrode active material NCM811 was 316.1 g / cm 2 , compacted density is 3.2g / cm 3 The surface density of the negative electrode active material AG used is 200 g / cm 2 , compacted density is 1.6g / cm 3 ; The active materials of both the negative and positive electrodes have been mixed with PVAs@LATP.
[0285] The assembled button cell was subjected to constant current charge and discharge test on the battery test system, with a voltage range of 3 to 4.2 V and a rate of 0.05C.
[0286] Comparative Example 4
[0287] 4.1 Preparation of LASTPF materials
[0288] Weigh 54.31 g of lithium carbonate, 20.39 g of aluminum oxide, 127.79 g of titanium dioxide, 333.58 g of diammonium phosphate, 3.70 g of ammonium fluoride, and 6.01 g of silicon dioxide, mix the precursors, and then sinter the precursors at a sintering temperature of 900° C. for 24 hours.
[0289] The above powder was dispersed in anhydrous ethanol solvent by planetary ball milling process, and an appropriate amount of grinding solution (grinding solvent to material ratio was 3:1) was added and ground for 3 h, wherein the ball to material ratio was 5.
[0290] 4.2 After grinding, the slurry is dried at 100°C. After drying, a powder agglomerated into a block is obtained, and the powder is ground with a mortar and passed through a 200-mesh sieve to obtain LASTPF powder.
[0291] 4.3 Preparation of polyvinyl alcohol fibers by electrospinning
[0292] A certain amount of polyvinyl alcohol solution was added to the aqueous solution, stirred at 80°C for 2 hours until it became a uniform polymer solution, and placed at room temperature for 12 hours. The electrospinning machine was used for spinning, with the polymer concentration set to 8%, the spinning flow rate to 0.3 ml / h, the humidity to 50%, the receiving distance to 15 cm, the voltage to 15 kV, the cabinet temperature to 25°C, and the prepared polyvinyl alcohol (PVAs) fibers were collected using a roller.
[0293] 4.4 Take 5 g of the PVAs fiber prepared above and 50 g of LASTPF, mix them thoroughly in an aqueous solution and stir for 8 h, and dry them in an oven at 100°C for 12 h to obtain PVA fiber-coated PVAs@LASTPF.
[0294] 4.5 Testing the ionic and electronic conductivity of PVAs@LASTPF
[0295] Take 3g of the above PVAs@LASTPF material. Use a mold with a diameter of 12mm, apply a pressure of 10MPa in a desktop powder tablet press, maintain the pressure for 15min, and then demold to obtain a PVAs@LASTPF sheet. Place the above sheet in a sintering furnace, heat it to 1000℃ at 3℃, and keep it warm for 15h. You can get a PVAs@LASTPF ceramic sheet. Use 1000-grit sandpaper moistened with alcohol to gently polish the surface of the above ceramic sheet according to the cross-cross method to remove surface impurities and ensure that the thickness of the electrolyte is uniform at all positions. Use a vernier caliper to measure the thickness of the ceramic sheet Lv4, use an ion sputtering instrument to evaporate gold blocking electrodes, and use AC impedance to test the ionic conductivity of PVAs@LASTPF, recorded as σv4.
[0296] Based on the principle of testing the electronic conductivity of powder by the four-probe method, the electronic conductivity of PVAs@LASTPF was tested. 10g of the above PVAs@LASTPF material was added to the powder resistance tester for testing. The electronic conductivity of the sample was tested at a pressure of 200MPa, which was recorded as ρv4.
[0297] 4.6 Positive Electrode Blending
[0298] Add a certain amount of ground NMP solvent (mass ratio of 1:20) to the above PVAs@LASTPF powder to obtain PVAs@LASTPF slurry. The particle size range of the powder is controlled at 200nm, and the positive electrode active material NCM811, the conductive agent carbon black SUPER-P, and the binder polyacrylamide are selected and dispersed in the NMP slurry of PVAs@LASTPF, wherein the mass ratio of NCM811, carbon black SUPER-P, polyacrylamide, and PVAs@LASTPF is 85:5:5:5, and stirred and mixed to prepare the positive electrode slurry.
[0299] 4.7 Negative electrode blending
[0300] The above-mentioned PVAs@LASTPF powder is added with a certain amount of ground NMP solvent (mass ratio of 1:20) to obtain PVAs@LASTPF slurry. The particle size range of the powder is controlled at 300nm, and the negative electrode active material AG, the conductive agent carbon black SUPER-P, and the binder polyacrylamide are selected and dispersed in the NMP slurry of PVAs@LASTPF, wherein the mass ratio of AG, carbon black SUPER-P, polyacrylamide, and PVAs@LASTPF is 85:5:5:5, and stirred and mixed to prepare the negative electrode slurry.
[0301] 4.8 Testing the electrochemical performance of the battery after blending
[0302] The above materials were prepared into CR2032 button batteries. The separator used was a PE separator with a thickness of 11 μm, and the surface density of the positive electrode active material NCM811 was 316.1 g / cm 2 , compacted density is 3.2g / cm 3 The surface density of the negative electrode active material AG used is 200 g / cm 2 , compacted density is 1.6g / cm 3 ; The active materials of both the negative and positive electrodes have been mixed with PVAs@LASTPF.
[0303] The assembled button cell was subjected to constant current charge and discharge test on the battery test system, with a voltage range of 3 to 4.2 V and a rate of 0.05C.
[0304] Comparative Example 5
[0305] 5.1 Preparation of polyvinyl alcohol fibers by electrospinning
[0306] A certain amount of polyvinyl alcohol solution was added to the aqueous solution, stirred at 80°C for 2 hours until it became a uniform polymer solution, and placed at room temperature for 12 hours. The electrospinning machine was used for spinning, with the polymer concentration set to 8%, the spinning flow rate to 0.3mL / h, the humidity to 50%, the receiving distance to 15cm, the voltage to 15kV, the cabinet temperature to 25°C, and the prepared polyvinyl alcohol (PVAs) fibers were collected using a roller.
[0307] 5.2 Preparation of PFCA-PVAs by hydrophobic treatment
[0308] The PVAs are treated to be hydrophobic. 50 g of the PVAs are dissolved in 100 g of ethanol solvent, and 5 g of perfluorooctanoic acid (PFCA) solution (concentration of the solution is 50%) is added. The mixture is stirred at room temperature for 4 hours, and perfluorooctanoic acid (PFCA) is grafted on the surface of the PVA polymer layer to obtain a polymer layer PFCA-PVAs with hydrophobic properties. The fibers are dried at 100°C. After drying, PFCA-PVAs can be obtained.
[0309] 5.3 Positive electrode blending
[0310] The above PFCA-PVAs are added to a certain amount of ground NMP solvent (mass ratio of 1:20) to obtain PFCA-PVAs slurry. The positive electrode active material NCM811, the conductive agent carbon black SUPER-P, and the binder polyacrylamide are selected and dispersed in the NMP slurry of PFCA-PVAs, wherein the mass ratio of NCM811, carbon black SUPER-P, polyacrylamide, and PFCA-PVAs is 85:5:5:5, and stirred and mixed to prepare the positive electrode slurry.
[0311] 5.4 Negative electrode blending
[0312] The above PFCA-PVAs are added to a certain amount of ground NMP solvent (mass ratio of 1:20) to obtain PFCA-PVAs slurry. The negative electrode active material AG, the conductive agent carbon black SUPER-P, and the binder polyacrylamide are selected and dispersed in the NMP slurry of PFCA-PVAs, wherein the mass ratio of AG, carbon black SUPER-P, polyacrylamide, and PFCA-PVAs is 85:5:5:5, and stirred and mixed to prepare the negative electrode slurry.
[0313] 5. Test the electrochemical performance of the battery after blending
[0314] The above materials were prepared into CR2032 button batteries, wherein the separator used was a PE separator with a thickness of 11 μm, and the active materials of the negative electrode and the positive electrode were mixed with PFCA-PVAs.
[0315] The assembled button cell was subjected to constant current charge and discharge test on the battery test system, with a voltage range of 3 to 4.2 V and a rate of 0.05C.
[0316] Table 1 Electrochemical performance test of the battery in the embodiments of the present invention and the comparative examples
[0317]
[0318]
[0319] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A modified composite solid electrolyte, characterized in that: include: A composite solid electrolyte, a flexible polymer fiber layer wrapped on the surface of the composite solid electrolyte, and a perfluorocarboxylic acid and / or a perfluorocarboxylate grafted on the flexible polymer fiber layer; The composite solid electrolyte is a solid electrolyte doped with cations and halogen anions; The cations are selected from transition metal cations and / or metalloid cations.
2. The modified composite solid electrolyte according to claim 1, characterized in that: The composite solid electrolyte is selected from lithium aluminum titanium phosphate doped with cations and halogen anions; And / or, the flexible polymer in the flexible polymer fiber layer is selected from one or more of polyester, polyamide, polyvinyl alcohol and polyacrylonitrile; and / or, the number of carbon atoms of the perfluorocarboxylic acid and / or perfluorocarboxylate is 4 to 12; And / or, the cation is selected from one or more of silicon ions, zirconium ions, tantalum ions and niobium ions.
3. The modified composite solid electrolyte according to claim 2, characterized in that: The molar ratio of cations, halogen anions and phosphorus in the lithium aluminum titanium phosphate doped with cations and halogen anions is (0.05-0.5): (0.05-0.5): (2.5-3); And / or, the mass ratio of the flexible polymer fiber layer to the composite solid electrolyte is 1:(5-20); And / or, the mass ratio of the total mass of the composite solid electrolyte and the flexible polymer fiber layer to the perfluorocarboxylic acid and / or perfluorocarboxylate is 5-50.
4. A method for preparing a modified composite solid electrolyte, characterized in that: The following steps are involved: S1) mixing a lithium source, an aluminum source, a titanium source, a phosphorus source, a compound containing a cation and a compound containing a halogen anion, sintering, and grinding to obtain a composite solid electrolyte; the cation is selected from transition metal cations and / or metalloid cations; S2) mixing the composite solid electrolyte and the flexible polymer fiber in water, and drying to obtain a composite solid electrolyte wrapped by the flexible polymer fiber; S3) mixing the composite solid electrolyte wrapped by the flexible polymer fiber with perfluorocarboxylic acid and / or perfluorocarboxylate in a solvent to obtain a modified composite solid electrolyte.
5. The preparation method according to claim 4, characterized in that: The lithium source is selected from one or more of lithium carbonate, lithium hydroxide, lithium nitrate, lithium oxalate, lithium bicarbonate and lithium oxide; The aluminum source is selected from aluminum oxide and / or aluminum hydroxide; The titanium source is selected from titanium dioxide and / or titanium trioxide; The phosphorus source is selected from one or more of phosphoric acid, diammonium phosphate and diammonium hydrogen phosphate; The cation-containing compound is selected from one or more of silicon dioxide, silicon dioxide, zirconium dioxide, niobium pentoxide, and tantalum pentoxide; The compound containing halogen anions is selected from one or more of ammonium fluoride, aluminum fluoride, calcium fluoride, ammonium chloride, calcium chloride, potassium chloride, ammonium bromide, potassium bromide, ammonium iodide and potassium iodide.
6. The preparation method according to claim 4, characterized in that: The molar ratio of the lithium source, aluminum source, titanium source, phosphorus source, cation-containing compound and halogen anion-containing compound is (0.5-1): (0.1-0.5): (1.3-1.8): (2.5-3): (0.05-0.5): (0.05-0.5).
7. The preparation method according to claim 4, characterized in that: The ball-to-material ratio in the step S1) is 5 to 20; The grinding is wet grinding; the mass ratio of the liquid medium to the sintered powder in the wet grinding is 2 to 5; The grinding time is 3 to 6 hours; And / or, grinding and sieving to obtain a solid electrolyte doped with cations and halogen anions; the mesh number of the sieving sieve is 80 to 400 meshes.
8. The preparation method according to claim 4, characterized in that: The flexible polymer fiber is prepared according to the following steps: A1) mixing the flexible polymer powder with the DMF solution and allowing to stand to obtain a spinning solution; A2) electrospinning the spinning solution to obtain flexible polymer fibers; The mass concentration of the flexible polymer in the spinning solution is 5% to 15%; The electrospinning flow rate is 0.2-0.5 mL / h; The humidity of the electrospinning is 40% to 60%; The receiving distance of the electrospinning is 10 to 20 cm; The voltage of the electrostatic spinning is 10-20 kV.
9. A battery, characterized in that: Including positive electrode, separator and negative electrode; The positive electrode comprises the modified composite solid electrolyte according to any one of claims 1 to 3 or the modified composite solid electrolyte prepared by any one of the preparation methods of claims 4 to 8; The negative electrode comprises the modified composite solid electrolyte according to any one of claims 1 to 3 or the modified composite solid electrolyte prepared by any one of the preparation methods of claims 4 to 8.
10. The battery according to claim 9, characterized in that The positive electrode comprises a positive electrode active layer; the particle size of the modified composite solid electrolyte in the positive electrode active layer is 50 to 600 nm; The mass concentration of the modified composite solid electrolyte in the positive electrode active layer is 0.5wt% to 10wt%; The negative electrode includes a negative electrode active layer; the particle size of the modified composite solid electrolyte in the negative electrode active layer is 50 to 600 nm; The mass concentration of the modified composite solid electrolyte in the negative electrode active layer is 0.5wt% to 10wt%.